Chronic Toxicity of Primary Metabolites of Chloroacetamide and Glyphosate to Early Life Stages of Marbled Crayfish Procambarus virginalis - Tresnakova, Nikola; Kubec, Jan; Stara, Alzbeta; Zuskova, Eliska; Faggio, Caterina; Kouba, Antonin; Velisek, Josef (Biology, 2022)
Degradation products of herbicides, alone and in combination, may affect non-target aquatic organisms via leaching or runoff from the soil. The effects of 50-day exposure of primary metabolites of chloroacetamide herbicide, acetochlor ESA (AE; 4 µg/L), and glyphosate, aminomethylphosphonic acid (AMPA; 4 µg/L), and their combination (AMPA + AE; 4 + 4 µg/L) on mortality, growth, oxidative stress, antioxidant response, behaviour, and gill histology of early life stages of marbled crayfish (Procambarus virginalis) were investigated. While no treatment effects were observed on cumulative mortality or early ontogeny, growth was significantly lower in all exposed groups compared with the control group. Significant superoxide dismutase activity was observed in exposure groups, and significantly higher glutathione S-transferase activity only in the AMPA + AE group. The gill epithelium in AMPA + AE-exposed crayfish showed swelling as well as numerous unidentified fragments in interlamellar space. Velocity and distance moved in crayfish exposed to metabolites did not differ from controls, but increased activity was observed in the AMPA and AE groups. The study reveals the potential risks of glyphosate and acetochlor herbicide usage through their primary metabolites in the early life stages of marbled crayfish.
Keywords: crayfish; metabolite; herbicide; ontogeny; toxicity; behaviour